Mandatory Procurement Lessons. Phenomena of External Initiator Factor - Blumberga Dagnija (Environmental and Climate Technologies, 2019)
Financial support is needed in order to implement renewable resources in countries energy sector in the shortest time period. Among the most important supports for European Union Member states are feed-in tariff and feed-in tariff premiums. This research analyses one country’s experience in applying subsidies of the electricity tariff that has caused public protests after 20 years. There are many reasons for this which are analysed in the paper. One of the most important reasons of high subsidies of energy tariffs – coincident mandatory procurement implementation of application of fossil fuel (imported natural gas) for cogeneration units, which has to be classified as external mover (initiator) factor. Energy sector’s potential development scenarios with or without support for renewable energy resources are being analysed in the paper.